Fang fiction : a novel - Stayman-London, Kate (The Dial Press, 2024)
"Tess Rosenbloom is used to living in the dark. She's a trauma survivor and chronic insomniac, the night manager of a chic Brooklyn hotel who spends her free time reading Blood Feud, a massively popular book series about two warring clans of vampires trapped on a mysterious Isle. Tess even dabbles in online conspiracies theorizing that the world of Blood Feud is real - it's fun to hunt for clues! But deep down, Tess doesn't believe vampires actually exist... Until one walks through her door. It turns out the sexy villain of Blood Feud is trapped, and his sister is desperate for Tess to help rescue him. Eager to escape her own life, Tess agrees, and soon she's in a fantasia of lavish palaces and dark forests, on a secret island where the sun never shines, everything is magical, and she's surrounded by deadly vampires - and against her better judgment, she's falling in love with one of them. Visiting the world of your favorite story is any fan's dream, but will Tess be able to outrun the demons of her past (and the vampires of her present) before it becomes a nightmare? In this darkly glamorous rom-com, Tess will find out whether it's worth risking her neck-and her heart-for a chance to reclaim her future"--